Prevalence of metabolically healthy obesity in medical students from the Universidad Nacional de Trujillo - Loje-López, Christian (2021)
Objective: To determine the prevalence of metabolically healthy obesity in medical students from the Universidad Nacional de Trujillo. Materials and methods: An observational descriptive cross-sectional research which included 37 medical students with obesity. Waist circumference (WC), systolic blood pressure (SBP), diastolic blood pressure (DBP), triglycerides (TG), serum HDL cholesterol (HDL-C) and glycemia were evaluated to classify the participants as having metabolically healthy obesity (MHO) or metabolically unhealthy obesity (MUO). Results: The prevalence of obesity in the medical students was 9.14 %. According to the Adult Treatment Panel III (ATP III), 78.38 % of the sample had MHO. Significant differences in HDL-C were found among the male students, and in SBP and DBPamong the students with MHO and MUO. According to the Wildman modified classification, the prevalence of MHO was 64.86 %, with significant differences in HDL-C among the male and female students, and in TG, SBP and DBP among the students with MHO and MUO. Conclusions: The prevalence of MHO in medical students from the Universidad Nacional de Trujillo is high.